The Implementation Of Teaching Reading By Using Comic To The Second Year Students Of SMP Negeri 11 Surakarta In 2011/2012 Academic Year - Gunawan, Gunawan (2012)
The objective of the study are to describe the implementation of teaching reading by using comics to the second year students of SMP N 11 Surakarta ,and to know the student's responses after being given the reading material by using comic. This research is aimed at knowing whether or not teaching reading by using comics can increase motivation and achievement of Junior High School students. The result of this study hopefully give contribution in Learning English. In this research, teaching reading by reading comic is used to increase students' motivation and their achievement in Learning English. This research is a descriptive qualitative research. The subject of the study is second year students of SMP N 11 Surakarta consisting of 42 students especially in class "VIII D". The object of the study in this research is the use of comics in teaching reading to the second year student of SMP N 11 Surakarta. The instruments used for collecting data are document , observation , and interview. The collected data are analyzed by using descriptive analysis. He describes the data by comparing the result test are used to know student's achievement. The mean of the student's achievement after the teacher gave the action 74,5% that belong to good cate gory and the students mean score before the teacher did the action was 51,15%, Based on the research finding, it can be concluded that teaching reading by using comics in teaching English could increase the student's motivation and achievement in reading comprehension. Therefore, it is better for the students to study English carefully through practice and experience, and to be active and creative in Learning English. While the teacher should teach the students with comics, process considerable knowledge to prepare the lesson they are going to teach as well as possible. Comic motivates the students by the pictures, comics as the story picture where the picture is important than the story. The use of colors, in reading comics the students can know the story just see the pictures. There are some advantages and disadvantages by reading comic, the students can train our reading comprehension in understanding the story. The students can get many vocabularies. The students can make their imagination develop.